Beauty premium and halal cosmetics industry - Ali, Saqib; Halim, Fairol; Ahmad, Norzieiriani (2016)
This paper provides some insight on an unexplored most emerging sector of Islamic marketing and economy “halal cosmetics”.Beauty is one of the biggest reality in this world everyone likes to look beautiful and beauty around, that’s why in modern age expense on cosmetics increase. Cosmetics are articles that used to increase beauty.There are many types and categories of cosmetics.Muslims are bound to religious requirements in every sphere of life, including cosmetics, therefore, there is a big scope for halal cosmetics industry to flourish and earn the profit. It is a source of marketing expansion. Non-Muslims also attract towards halal cosmetics for its natural, environmentally friendly and green ingredients.Facts and figures also show evidence that halal perspective of cosmetics is a matter of concerns for consumers, producers, manufacturers, and marketers.